Indonesian Batik Study of Go Tik Swan at 1950-1990 Period in Surakarta - GRAFITA, AFRIK; Rudianto, M. (Faculty Of Arts and Design Sebelas Maret University, 2023)
Batik is very closely related to the Majapahit Empire and Islamic kingdoms in Java in the past. The development of batik incessantly took place during the Mataram kingdom in 1600-1700. During this time, batik spread throughout Java, where it was used for ceremonial purposes and attire for royalty, and the craftsmen of the palace artists created various kinds of batik motifs. The treasury of batik designs developed from a variety of aesthetic orientations, in Central Java's palaces, designs were often inspired by ritual. The spread of batik culture to the birth of coastal batik, its emergence is a new period in the world of batik. This period deserves to be called modern batik, the form of coastal batik has developed very widely with various cultural influences brought by immigrants. One of the pioneers in the world of batik in Surakarta City is Go Tik Swan Panembahan Hardjoanagoro, he is the creator of the birth of Indonesian Batik which was inspired by President Soekarno's orders. Indonesian batik is a sophisticated blend of batik elements in the archipelago, namely classic batik and coastal batik in the design of the motifs and the use of colors. Go Tik Swan makes the concept of semi-delinquent as the basis for creating inner masterpieces. Indonesian batik is modern and multi-colored, but does not leave its roots, namely Javanese culture in terms of design motifs, production processes, and their meanings. The aims of this study were to study the rationale for Indonesian Batik based on the concept of semi-deferred by Go Tik Swan, to know the process of creating and realizing Indonesian Batik, and to understand the role of